Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1029/2017jg004227
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Response of Respiration Across the Heterogeneous Landscape of the Alaskan Arctic Tundra

Abstract: Predictions of the response of ecosystem respiration to warming in the Arctic are not well constrained, partly due to the considerable spatial heterogeneity of these permafrost-dominated areas. Accurate calculations of in situ temperature sensitivities of respiration (Q 10 ) are vital for the prediction of future Arctic emissions. To understand the impact of spatial heterogeneity on respiration rates and Q 10 , we compared respiration measured from automated chambers across the main local polygonized landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 137 publications
(191 reference statements)
1
16
0
1
Order By: Relevance
“…Ideally, COS would be used to validate other flux-partitioning methods and to assess assumed relations, such as the relation between respiration and temperature that is used to determine GPP NEE (28). Recent studies in a temperate deciduous forest and an Arctic tundra have found that the standard flux-partitioning technique typically overestimates daytime ecosystem respiration and thereby overestimates GPP (32, 33). Here we find that GPP COS-fit is 13% higher than GPP NEE .…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, COS would be used to validate other flux-partitioning methods and to assess assumed relations, such as the relation between respiration and temperature that is used to determine GPP NEE (28). Recent studies in a temperate deciduous forest and an Arctic tundra have found that the standard flux-partitioning technique typically overestimates daytime ecosystem respiration and thereby overestimates GPP (32, 33). Here we find that GPP COS-fit is 13% higher than GPP NEE .…”
Section: Resultsmentioning
confidence: 99%
“…, 1980; Wilkman et al. , 2018; Zona et al. , 2011).…”
Section: Methodsunclassified
“…The organic C content in the top 100 cm of these soils ranges from 37 to 139 kg m −3 (Bockheim et al, 2004), and soil bulk density of the organic layer in the study site is 0.06 g cm -3 on average (Lipson et al, 2013). Much of the study site is patterned ground with many polygons, producing microtopographical and hydrological heterogeneity, where polygon rims (BEC) are associated with a lower water table and drier conditions, and low-centered polygons centers (BES) and troughs have a higher water table and wetter conditions (Brown et al, 1980;Wilkman et al, 2018;Zona et al, 2011). As determined by 14 C dating, the soil age of the drained lake site of this study is classified as a "medium" age (50-300 YBP, Hinkel et al, 2003); within the drained lake, soil pH values range from 5.1 at the low center polygons to 4.5 at polygon rims (Hinkel et al, 2003;Lipson et al, 2012).…”
Section: Site Descriptionmentioning
confidence: 97%
“…Other studies demonstrated that Q10 varies with environmental conditions, ecosystem types, and soil texture (Meyer et al, 2018;Graf et al, 2011;Kim et al, 2019), showing 45 a large spatial heterogeneity with generally higher values in the high-latitudinal regions (Zhou et al, 2009). In addition, Wilkman et al (2018) reported a temporal heterogeneity in Q10 over the Alaskan Arctic Tundra and suggested a higher value (e.g., 2.45) for early summer (e.g., June) but lower value (e.g., 1.58 to 1.67) for the peak growing season (e.g., July).…”
Section: Introductionmentioning
confidence: 95%